SUBSURFACE STRUCTURES ANALYSIS BASED ON THE 3D GEOMAGNETIC DATA INVERSION MODELLING OF SUMANI SEGMENT, WEST SUMATERA - Partogi, Jonathan
The Sumatran Fault is one of the faults with relatively high tectonic activites. This fault consists of 19 segments. One of its segement is Sumani Segment. This study did a 3D inversion on the Sumani Segment’s area to get informations about subsurface structures on the area traversed by the Sumani Segment. The data of geomagnetic method survey was chosen as it is method mostly used in mapping a large area. This study shows the magnetic anomalies are in the range between 400 nT to -350 nT. Then, the study conducted upward continuation until the optimum elevation was reached which was 5000 m. The upward continuation result shows the range of the magnetic anomalies starts from 200 nT to -200 nT. This change is caused by the attenuation of shallow anomalies. The magnetic anomaly maps and the inversion model were used for the qualitative and quantitative interpretation. The inversion model itself shows the susceptibility ranging from 2,5 x 10-7 to 1,71 SI. The model shows the strike slip mechanism at the Sumani Segment. The fault at Sumani Segment overlaps with the Sianok Segment eventually forming the Singkarak Lake